Sistem Informasi Pemesanan Pada Ann Printing Berbasis Website - Elsa Monika Affiani; Novita Mariana (LPPM STIKOM Tunas Bangsa, 2023)
The use of the internet plays an important role in exchanging data and information. Ann printing is a convection engaged in screen printing design services such as t-shirts, polo shirts, hoodies and others. At the time of carrying out sales transactions, it was still carried out using a manual sales system such as the use of social media and did not have a personal website. Currently, the problems faced in making transactions are still done manually using sales notes, sometimes these notes are not immediately recapitulated into a ledger, resulting in lost sales notes, besides that consumers experience time management problems in getting a confirmation of receipt of goods. Based on the research results, it is proposed to create a sales information system website with built-in features that can generate sales data, print invoices and make it easier for consumers to get a confirmation regarding the estimated collection of goods in a timely manner.